Early Predictive Values for Severe Rhabdomyolysis in Blunt Trauma - Jung Yun Park; Myoung Jun Kim; Jae Gil Lee (Journal of Trauma and Injury)
Purpose Rhabdomyolysis (RB) is a syndrome characterized by the decomposition of striated muscles and leakage of their contents into the bloodstream. Acute kidney injury (AKI) is the most significant and serious complication of RB and is a major cause of mortality in patients with RB. Severe RB (creatine kinase [CK] ≥5,000) has been associated with AKI. However, early prediction is difficult because CK can reach peak levels 1–3 days after the trauma. Hence, the aim of our study was to identify predictors of severe RB using initial patient information and parameters. Methods We retrospectively analyzed 1,023 blunt trauma patients admitted to a single tertiary hospital between August 2011 and March 2018. Patients with previously diagnosed chronic kidney disease were excluded from the study. RB and severe RB were defined as a CK level ≥1,000 U/L and ≥5,000 U/L, respectively. The diagnosis of AKI was based on RIFLE criteria. Results The overall incidence of RB and severe RB was 31.3% (n=320) and 6.2% (n=63), respectively. On multivariable analysis, male sex (odds ratio [OR] 3.78, 95% confidence interval [CI] 1.43 to 10.00), initial base excess (OR 0.85, 95% CI 0.80 to 0.90), initial CK (OR 2.07, 95% CI 1.67 to 2.57), and extremity abbreviated injury scale score (OR 1.78, 95% CI 1.39 to 2.29) were found to predict severe RB. The results of receiver operating characteristic analysis showed that the best cutoff value for the initial serum CK level predictive of severe RB was 1,494 U/L. Conclusions Male patients with severe extremity injuries, low base excess, and initial CK level >1,500 U/L should receive vigorous fluid resuscitation.